Get Out the Vote : How to Increase Voter Turnout - Green, Donald P., 1961-; Gerber, Alan S. (Book collections on Project MUSE., 2015)
The most important element in every election is getting voters to the polls?these get-out-the-vote (GOTV) efforts make the difference between winning and losing office. With the first two editions of Get Out the Vote, Donald P. Green and Alan S. Gerber broke ground by introducing a new scientific approach to the challenge of voter mobilization that profoundly influenced how campaigns operate. Get Out the Vote has become the reference text for those who manage campaigns and study voter mobilization. In this expanded and updated edition, Green and Gerber incorporate data from more than 100 new studies, which shed new light on the costeffectiveness and efficiency of various campaign tactics, including door-todoor canvassing, email, direct mail, and telephone calls. Two new chapters focus on the effectiveness of registration drives and messaging tactics. The new Get Out the Vote will be available as the country gears up for the 2016 presidential campaign. This readable, practical guide on voter mobilization is sure to be an important resource for consultants, candidates, and grassroots organizations, as well as a valuable teaching tool in courses on campaigns and elections. Praise for Previous Editions: "Green and Gerber have studied turnout for years. Their findings, based on dozens of controlled experiments done as part of actual campaigns, are summarized in ... Get Out the Vote, which is bound to become a bible for politicians and activists of all stripes."?Alan Krueger in the New York Times " Get Out the Vote shatters conventional wisdom about GOTV."?Hal Malchow in Campaigns and Elections "Green and Gerber's recent book represents important innovations in the study of turnout."? Political Science Review "Green and Gerber have provided a valuable resource for grassroots campaigns across the spectrum."? National Journal